58.3k views
3 votes
Convert y - 2 = -4(x - 12) to standard form.

Convert y - 2 = -4(x - 12) to standard form.-example-1

2 Answers

4 votes
The answer is 4x+y=50.
To solve this, first you have to expand the right side of the equation. This leaves you with y-2= -4x+48.
Then, you add two to both sides of the equation leaving you with y= -4x+50.
Finally, you add 4x to both sides of the equation leaving you with 4x+y=50.

Hope this helps! Have a great day!
User Eran
by
6.1k points
5 votes
Hello, there!



y - 2 = -4(x - 12)

First, let's simplify the right side by using the distributive property.

-4 * x = -4x

-4 * -12 = 48

Now, we have:


y - 2 = -4x + 48

Now, let's the equation to make the right side only contain y.


y - 2 = -4x + 48
+2 +2

Now, we have:

y = -4x + 50

Finally, to make this equation standard form (
Ax + By = C), we must add 4x to each side



y = -4x + 50
+4x +4x

Our final answer is:


4x + y = 50

This means that the correct answer is A.


I hope I helped!

Let me know if you need anything else!

~ Zoe
User Sam Rao
by
5.4k points